The role of Kuniran (U. moluccensis) and Gurami (O. goramy) fish thorns and scales in increasing salivary leukocyte and monocyte cells viability against Streptococcus mutans - I Dewa Ayu Ratna Dewanti; I Dewa Ayu Susilawati; P. Purwanto; Pujiana Endah Lestari; Roedy Budirahardjo; Dyah Setyorini; Ristya Widi Endah Yani; Erawati Wulandari; Melok Aris Wahyukundari (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Kuniran thorns and Gurami fish scales are rich in protein and minerals such as dentin believed to increase cell viability against Streptococcus mutans (S. mutans) that causes dental caries. These, in turn, can cause systemic diseases if left untreated. Purpose: This study aims to analyze the influence of Kuniran thorns and Gurami fishes scales on the viability of monocytes and salivary leukocytes against S. mutans. Methods: Monocytes and leukocytes salivary cells were placed on a microtiter plate and treated according to the nature of each group. This study comprised the following groups: control group: untreated; S. mutans group: induced by S. Mutans; Gurami thorn group: thorns + S. Mutans; Gurami scales group: scales + S. Mutans; Kuniran thorn group: thorns + S. Mutans; Kuniran scales group: scales + S. mutans. Viability analysis involved staining with Tripan Blue. Furthermore, the number of viable cells (white) was calculated under an inverted microscope at 200 times magnification from five fields of view. Data was analyzed by means of an ANOVA test followed by LSD test. Results: The ANOVA and LSD tests confirmed significant differences (0.01<P). Kuniran thorns and Gurami fish scales increased the viability of monocytes and salivary leukocytes, but not significantly. The content of flavonoids, amino acids, omega 3, omega 6 and antioxidants increased leukocyte metabolism, thereby increasing cell resistance to S. mutans infection. Conclusion: Kuniran thorns (U. moluccensis) and Gurami (O. goramy) fish scales increase the viability of salivary leukocyte and monocyte cells against Streptococcus mutans.